2016
DOI: 10.12659/msm.897385
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Left Atrial Energy Loss and Mechanics Abnormalities in Diabetic Patients with Normal Left Atrial Size: A Study Combining Vector Flow Mapping and Tissue Tracking Echocardiography

Abstract: BackgroundWhether left atrial (LA) functional abnormalities already exist when the LA is of normal size is unknown. The aim of this study was to explore LA energy loss and mechanics changes using vector flow mapping (VFM) and two-dimensional tissue tracking (2DTT) echocardiography in patients with diabetes and normal LA size.Material/MethodsThis study included 47 normotensive patients with diabetes and 45 controls. The following indexes were measured: LA energy loss during systole (LAELs), early diastole (LAEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…In our study, we did not find an association between LA strain and duration of diabetes or HbA1c, possibly due to the early stage of diastolic dysfunction detected. Prior echocardiographic data support a primary atrial myopathy in diabetes [27, 28]. Our study demonstrated alterations of conduit longitudinal strain and motion fraction, changes which are supportive of primary alterations of LV relaxation associated with mild diastolic dysfunction [29].…”
Section: Discussionsupporting
confidence: 75%
“…In our study, we did not find an association between LA strain and duration of diabetes or HbA1c, possibly due to the early stage of diastolic dysfunction detected. Prior echocardiographic data support a primary atrial myopathy in diabetes [27, 28]. Our study demonstrated alterations of conduit longitudinal strain and motion fraction, changes which are supportive of primary alterations of LV relaxation associated with mild diastolic dysfunction [29].…”
Section: Discussionsupporting
confidence: 75%
“…Vorticity represents the direction and strength of local vortex rotation. Numerous investigations have confirmed the utility of these new parameters …”
Section: Introductionmentioning
confidence: 85%
“…The optimized blood flow dynamics can reflect the general function of left ventricle and the ability of cardiovascular system in maintaining the relative stabilization of blood circulation . The change in intra‐ventricular blood flow‐pattern is related to the diastolic filling .…”
Section: Introductionmentioning
confidence: 99%
“…Blood flow patterns inside the cardiac chamber are affected by the anatomical structure of the heart and valves, as well as the motion of myocardial and intracardiac pressure. Together, these factors generate the flow order reflecting normal or pathological physiology . Energy loss (EL) is a new hemodynamic index for assessing cardiac function that is caused by friction produced between the flowing blood and wall shear flow due to blood viscosity, which converts kinetic energy to heat.…”
Section: Introductionmentioning
confidence: 99%